The typology problem and the doxastic approach to delusions - Pablo Lopéz-Silva (Filosofia Unisinos, 2016)
This paper explores one of the most fundamental philosophical worries underlying the occurrence of delusions, namely, the problem about the specific type of mental state that grounds a delusional report or, as I shall call it, ‘the typology problem’. The analysis is developed as follows: (i) After formulating and circumscribing the target problem, (ii) I explore the main tenets and advantages of the doxastic view of delusions, perhaps, the strongest candidate currently available within the typology debate. (iii) After, I clarify and evaluate four of the main counter-arguments against the doxastic view offering a number of counter replies to these attacks. (iv) Finally, I conclude that the anti-doxastic argumentation offers no good reasons to abandon the doxastic model and that this model does not need to appeal to external resources to reply to such counter-arguments. At the same time, I finalize with some of the challenges that remain open within the doxastic view.